Polar stratospheric cloud observations by MIPAS on ENVISAT: detection method, validation and analysis of the northern hemisphere winter 2002/2003 - Spang, R.; Remedios, J. J.; Kramer, L. J.; Poole, L. R.; Fromm, M. D.; Müller, M.; Baumgarten, G.; Konopka, P. (CCSD, 2005)
International audience The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) on ENVISAT has made extensive measurements of polar stratospheric clouds (PSCs) in the northern hemisphere winter 2002/2003. A PSC detection method based on a ratio of radiances (the cloud index) has been implemented for MIPAS and is validated in this study with respect to ground-based lidar and space borne occultation measurements. A very good correspondence in PSC sighting and cloud altitude between MIPAS detections and those of other instruments is found for cloud index values of less than four. Comparisons with data from the Stratospheric Aerosol and Gas Experiment (SAGE) III are used to further show that the sensitivity of the MIPAS detection method for this threshold value of cloud index is approximately equivalent to an extinction limit of 10 -3 km -1 at 1022nm, a wavelength used by solar occultation experiments. The MIPAS cloud index data are subsequently used to examine, for the first time with any technique, the evolution of PSCs throughout the Arctic polar vortex up to a latitude close to 90° north on a near-daily basis. We find that the winter of 2002/2003 is characterised by three phases of very different PSC activity. First, an unusual, extremely cold phase in the first three weeks of December resulted in high PSC occurrence rates. This was followed by a second phase of only moderate PSC activity from 5-13 January, separated from the first phase by a minor warming event. Finally there was a third phase from February to the end of March where only sporadic and mostly weak PSC events took place. The composition of PSCs during the winter period has also been examined, exploiting in particular an infra-red spectral signature which is probably characteristic of NAT. The MIPAS observations show the presence of these particles on a number of occasions in December but very rarely in January. The PSC type differentiation from MIPAS indicates that future comparisons of PSC observations with microphysical and ...